2004
DOI: 10.1093/hmg/ddh153
|View full text |Cite
|
Sign up to set email alerts
|

Null mutation of calpain 3 (p94) in mice causes abnormal sarcomere formation in vivo and in vitro

Abstract: The giant protein titin serves a primary role as a scaffold for sarcomere assembly; however, proteins that mediate this remodeling have not been identified. One potential mediator of this process is the protease calpain 3 (C3), the protein mutated in limb girdle muscular dystrophy type 2A. To test the hypothesis that C3 mediates remodeling during myofibrillogenesis, C3 knockout (C3KO) mice were generated. The C3KO mice were atrophic containing small foci of muscular necrosis. Myogenic cells fused normally in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
179
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(199 citation statements)
references
References 47 publications
18
179
1
1
Order By: Relevance
“…This might explain why we observed very little colocalisation of telethonin with Z-disk titin in homozygous targeted cells, if this localisation is dependent on its phosphorylation by the TK. Although a muscle-specific calpain (calpain-3, or p94), a Ca 2+ -activated protease, implicated in limb girdle muscular dystrophy type 2A (Kramerova et al, 2004) has also been reported to interact with M-band titin (Sorimachi et al, 1995), this protein is not expressed in the heart, and thus effects on calpain 3 will not contribute to the phenotype we observe here.…”
Section: Discussionmentioning
confidence: 74%
“…This might explain why we observed very little colocalisation of telethonin with Z-disk titin in homozygous targeted cells, if this localisation is dependent on its phosphorylation by the TK. Although a muscle-specific calpain (calpain-3, or p94), a Ca 2+ -activated protease, implicated in limb girdle muscular dystrophy type 2A (Kramerova et al, 2004) has also been reported to interact with M-band titin (Sorimachi et al, 1995), this protein is not expressed in the heart, and thus effects on calpain 3 will not contribute to the phenotype we observe here.…”
Section: Discussionmentioning
confidence: 74%
“…No "hot point" was found, making diagnosis of the disease very difficult. Capn3 knockout mice showed a human calpainopathy-like phenotype though milder than that of humans [82,134], indicating that calpainopathy is caused by defects in the gene for calpain-3/p94. A primary cause of LGMd2A is a defect in the protease activity, not the structural properties, of calpain-3/p94 [121].…”
Section: Skeletal Muscle-specific Calpain Calpain-3/p94mentioning
confidence: 96%
“…Four-and-a-half LIM domain protein 2 (FHL2) recruits metabolic enzymes to sites of high energy consumption such as the M-band and the cardiac N2B region within the I-band (Lange et al, 2002). Titin's N2A region binds muscle ankyrin repeat proteins, which link myofibrillar stretch-induced signaling pathways and muscle gene expression (Miller et al, 2003) and the protease calpain 3 (p94), which has been suggested to play a role in myofibrillogenesis and sarcomere remodeling (Sorimachi et al, 1995;Kramerova et al, 2004). Additional binding sites for proteins related to signal transduction and protein degradation, such as MuRF (muscle-specific RING finger protein) 1 and 2 and calpain 3 are located at titin's M-band (Kinbara et al, 1997;Centner et al, 2001;Lange et al, 2002;Witt et al, 2005).…”
Section: Generation and Validation Of The Animal Modelmentioning
confidence: 99%